Новий рукопис "Історії Челебі Акая" - Сейтяг'яєв, Н. (Слово і Час, 2017)
У статті розглядаються особливості нового рукопису “Історії Челебі Акая”, виявленого в Бібліотеці раритетних творів Стамбульського університету 2014 р. Новий рукопис звірено з чотирма відомими списками історичного твору Челебі Акая, які зберігаються в Бахчисараї, Києві, Санкт-Петербурзі та Каїрі. До звірки залучені також три стамбульські списки “Семи планет” Мухаммеда Різи та унікальний рукопис ‘"Умдет аль-ахбар” Абдульгаффара Киримі. У ході дослідження з'ясовано час написання твору (1754) й ім'я автора (Абдуррахман б. Мухаммед аль- Хапьветі), встановлено дві відомі нині авторські редакції цього твору. The article provides information on basic features of the new-found manuscript of “History of Chelebi Aqai”. The copy was discovered in the Istanbul University Rare Works Library in 2014. The research is based on the comparison of this new manuscript and four known copies of Chelebi Aqai's historical work from Bakhchysarai, Kyiv, St. Petersburg and Cairo. Three Istanbul manuscript copies of Muhammed Riza’s “Seven planets” and the unique Istanbul manuscript of 'Abd al-Ghaffar Qyrymi's “Umdet al-akhbar” were also taken for comparison. The study of Istanbul manuscript of “History of Chelebi Aqai” allowed determining the time of writing (1754) and the name of the author (Abd al-Rahman b. Muhammad al-Khalveti). It is established that now we have two author's versions of this work. В статье рассматриваются особенности новой рукописи “Истории Челеби Акая”, обнаруженой в Библиотеке раритетных произведений Стамбульского университета в 2014 г. Осуществлена сверка новой рукописи с четырьмя известными рукописями исторического произведения Челеби Акая из Бахчисарая, Киева, Санкт-Петербурга и Каира. К сверке привлечены также 3 стамбульские списка “Семи планет’ Мухаммеда Ризы, а также уникальная рукопись “Уйдет ал-ахбар” 'Абд ал-Гаффара Кырыми. В ходе исследований стамбульской рукописи “Истории Челеби Акая” выяснено время написания произведения (1754) и имя автора (Абд ар-Рахман б. Мухаммед ап- Хальвеги), установлено две известны в настоящее время авторские редакции этого произведения.